Electricity from Wood: A Wood Quality and Energy Efficiency Approach to Small Scale Pyro-gasification. (10th June 2016) - Fellin, Marco; Negri, M.; Macrì, G.; Bernardi, B.; Benalia, S.; Zimbalatti, G.; Andrea, R. Proto
Abstract: The global demand for renewable energy in the last years is facing innovations like the co-generation of electricity and heat from wooden industrial residues and biomass. Wood gasification is a very promising technique for conversion of wood chemical energy into thermal energy and into electricity. A new generation of small scale, moderately priced and easy to install pyro-gasification plants became available on the market, being an opportunity for the SMEs. These systems are also characterized by a remarkable operational easiness and great versatility in the type of used biomass, which can range from industrial residues (sawdust, wood chips...) to biomass of forestry and non-forestry origin. This study performed an extensive testing of a small size pyro-gasification plant capable of producing 30 kW of electricity and 30 kW of thermal energy, both net to enter in the network of GSE (Energy Services Manager) via the feed-in tariff and in a small district heating network or other uses. The process of pyro-gasification is analyzed in its entirety by a characterization of input biomass, pyro-gasification process monitoring, analysis of the quality of the produced syngas, characterization of residues due to the process (washing water smoke, charcoal...) and verification of the total efficiency. The electric efficiency of the system, from hardwood to syngas to electricity is quantified in being 12%.